FISH DIVERSITY OF GHODAGHODI LAKE IN KAILALI, FAR-WEST NEPAL - Joshi, Dipendra; K. C., Bijaya (Journal of Institute of Science and Technology, 2017)
Ghodaghodi Lake is an ox-bow perennial lake of Ghodaghodi Lake Complex, situated in Kailali district. The present study was conducted to understand the fish diversity, community structure and distribution pattern in Ghodaghodi Lake. A total of 13 fish species were recorded from the different section of Ghodaghodi Lake, belonging to five order, eight family and eleven genera. According to fish catch the dominant order and family of Ghodaghodi Lake were found to be Cypriniformes (40%) and Cyprinidae (40%) respectively. The dominant fish species of Ghodaghodi Lake was Labeo gonius followed by Mystus tengara, Nandus nandus and Channa striatus. The highest diversity index (2.46), species richness (6.14) and evenness (0.96) of fish were recorded from station III during the month of January. Lowest diversity index (1.75) and evenness (0.90) was found in station II and during the month of October (2.25 and 0.88). Similarly, lowest species richness was found in station I (3.91) and during the month of July (5.82). Fish diversity and number in Ghodaghodi Lake were found to have decreased. This could be due to pollution, illegal fishing and excessive proliferation of aquatic weeds. Journal of Institute of Science and Technology Volume 22, Issue 1, July 2017, page: 120-126